Advanced Co3O4–CuO nano-composite based electrocatalyst for efficient hydrogen evolution reaction in alkaline media. (8th October 2019) - Tahira, Aneela; Ibupoto, Zafar Hussain; Willander, Magnus; Nur, Omer
Abstract: In this study, we incorporate a copper impurity into (Co3 O4 ) nanowires precursor that turn them into an active catalyst for the hydrogen evolution reaction in 1M KOH. The XRD and XPS results are in good agreement and confirmed the formation of Co3 O4 –CuO nano-composite by wet chemical method. To date, the performance of hydrogen evolution reaction in alkaline for the composite catalyst is comparable or superior to cobalt oxide based HER electro-catalysts. The HER catalyst exhibits the lowest Tafel slope of 65 mVdec −1 for the cobalt-based catalysts in alkaline media. A current density of 10 mA/cm 2 is achieved at a potential of 0.288 V vs reversible hydrogen electrode (RHE). The mixed transition metal oxide Co3 O4 –CuO based HER electro-catalyst is highly stable and durable. The EIS results demonstrates that HER is highly favorable on the Co3 O4 –CuO due to the relatively small charge transfer resistance (173.20 Ohm) and higher capacitance values (1.97 mF). Highlights: Advanced Co3 O4 –CuO nano-composite for efficient hydrogen evolution reaction. The excellent stability and durability is demonstrated. The efficient hydrogen evolution reaction due to small charge transfer resistance.